Genre und Gemeinsinn Hollywood zwischen Krieg und Demokratie - Kappelhoff, Hermann (Cinepoetics, 2016)
Based on the premise that a society`s sense of commonality depends upon media practices of political communitarization, this study examines how Hollywood was deployed during the Second World War. It shows that Hollywood responded to the crisis of democracy in the war by creating a new genre. Using an affective theory of genre cinema, it offers a new characterization of the relationship between politics and poetics in forming commonality.